(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Excavation activities carried out near existing foundations can significantly alter the stress state of the surrounding soil, resulting in reduced bearing capacity and increased settlement that may compromise the stability and serviceability of structures. This issue is particularly important in urban areas, where new construction is frequently undertaken adjacent to existing buildings with limited available space. The present study evaluates the effectiveness of geogrid reinforcement in improving the performance of strip foundations subjected to the influence of nearby excavations through numerical modelling using PLAXIS 2D. A series of finite element analyses was performed by varying the excavation depth and horizontal distance from the existing strip foundation to assess their effects on foundation behaviour. Both reinforced and unreinforced soil conditions were analysed under identical loading and boundary conditions to enable a systematic comparison of their performance. The response of the foundation system was evaluated in terms of ultimate bearing capacity and settlement. The numerical results demonstrate that the incorporation of geogrid reinforcement effectively mitigates the adverse effects of adjacent excavation by improving the load-carrying capacity of the foundation soil and limiting excessive deformation. Depending on the excavation geometry, the reinforced soil exhibited an increase in ultimate bearing capacity ranging from 14% to 27%, while the corresponding settlement decreased by approximately 11% to 16% compared with the unreinforced condition. The improvement is attributed to the ability of the geogrid to provide tensile reinforcement, enhance stress distribution, and improve soil confinement beneath the foundation. Overall, the study demonstrates that geogrid reinforcement is an effective ground improvement technique for maintaining the stability and performance of existing strip foundations subjected to nearby excavation, thereby providing useful guidance for the design and rehabilitation of foundation systems in urban construction projects.